2011
DOI: 10.1089/nat.2010.0274
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Transfection Rates of Small-Interfering RNA Using Dioleylglutamide-Based Magnetic Lipoplexes

Abstract: Magnetic force-guided delivery (magnetofection) has been studied as a new modality for introducing small-interfering RNA (siRNA) into target cells, but its delivery efficiency needs to be improved. Here, we report that magnetofection of N,N''-dioleylglutamide (DG)-based magnetic lipoplexes can substantially enhance the cellular delivery rates of siRNA. The siRNA was triply complexed with DG-based cationic liposomes and cationic iron-oxide nanoparticles. The formation of siRNA-containing magnetic lipoplexes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…We observed a physiological knock-down of actin in HeLa cells, in a dose-dependent manner, as observed using the adhesion assay. Others have successfully knocked-down various genes in HeLa cells or other cell lines using a combination of cationic liposomes and/or magnetofection with a stationary magnet [28], [29], [30]. While transfection efficiencies of siRNA between lipid methodology and magnetofection were similar, the significant difference is one of viability – with lipid methodology causing greater cell death compared to magnetofection [31].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a physiological knock-down of actin in HeLa cells, in a dose-dependent manner, as observed using the adhesion assay. Others have successfully knocked-down various genes in HeLa cells or other cell lines using a combination of cationic liposomes and/or magnetofection with a stationary magnet [28], [29], [30]. While transfection efficiencies of siRNA between lipid methodology and magnetofection were similar, the significant difference is one of viability – with lipid methodology causing greater cell death compared to magnetofection [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, magnet‐labeled cells, obtained by internalization of IONs, could allow magnet‐derived retention and accumulation at target sites which could boost therapeutic effects. To elevate efficiency of magnet‐derived gene transfer for genetic engineering of therapeutic cells, design and application for novel iron oxide based carriers including micelles, liposomes, and nanoparticles have been intensively studied …”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles coated with hydrophilic polymers can be loaded within the core of liposomes or attached to the surface of liposomes via ionic interactions. Commercial cationic iron oxide nanoparticles (CombiMAG, Chemicell GmbH) has been complexed with N,N″-dioleylglutamide (DG)-based lipoplexes/siRNA via electrostatic interactions for magnetically-driven delivery of therapeutic siRNA against Mcl1 gene [68]. By measuring the amounts of transfected cells with fluorescence-labeled siRNAs using flow cytometry, the investigators demonstrated that the exposure of CombiMAG/lipoplexes/siRNA complexes to a magnetic field for 15 min significantly increased the efficiency of intracellularly delivered siRNA by 2–5-fold in various types of cancer cells studied, including human lung cancer, breast cancer, and cervical cancer cells.…”
Section: Formulations Of Spion-based Carriersmentioning
confidence: 99%
“…Polyarginine, polylysine, and PEI were conjugated to PEG immobilized SPIONs to attach siRNAs via ionic interactions and escape from endosome [93]. The cationic liposomes composed of N,N-dioleylglutamide were complexed with siRNAs to form lipoplexes, which subsequently mixed with cationic iron oxide nanoparticles (CombiMAG) [68]. In the presence of an external magnetic field, intracellular uptake of lipoplexes/iron oxide nanoparticles mostly occurs within 30 min, while intracellular delivery by conventional lipoplexes takes more than 3 hrs in vitro .…”
Section: Applications Of Spion-based Delivery Systems For Biotheramentioning
confidence: 99%
See 1 more Smart Citation